Mathematical modelling of an infilled RC frame structure based on the results of pseudo-dynamic tests. - Dolsek, Matjaz (Earthquake engineering & structural dynamics.)
In this paper, a technique is presented which employs the results of pseudo-dynamic tests for the development of a mathematical model. This technique, described by means of the mathematical modelling of a three storey reinforced concrete frame building with infill in the bottom two storeys, which was tested at ELSA in Ispra, proved to be effective and to lead to a fairly accurate structural model. The results of analyses suggest that the global non-linear seismic response of reinforced concrete frames with masonry infill can be adequately simulated by a relatively simple mathematical model, which combines beam elements with concentrated plasticity, simple connection elements, and equivalent strut elements representing the infill walls (provided that the infill does not fail out of plane and that no shear sliding failure occurs.